MACROSCOPIC ANATOMY OF THE MAMMARY GLAND IN THE LLAMA (LAMA GLAMA) - Chávez R., Alexander (2010)
The present study aimed to identify and describe the structures of the mammary glands and related structures of the llama (Lama glama). Five adult females in lactation were embalmed using a 12% formalin solution. Superficial and deep dissections were done; comparing both sides of the glands and observing related structures as muscles, arteries, veins, nerves and lymph nodes. Macroscopic characteristics of the udder were similar to other camelids and mammals; however, there was a different arterial vessel pattern. Also, was observed the presence of the supramammary lymphatic nodule, not described in other domestic animals. The nipple presented two output ducts that join into one.